2015
DOI: 10.1007/s11418-015-0928-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion

Abstract: Aloperine (ALO), one of the alkaloids isolated from Sophora alopecuroides L., is traditionally used for various diseases including neuronal disorders. This study investigated the protective effects of ALO on neonatal rat primary-cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion (OGD/RP). Treatment with ALO (25, 50, and 100 mg/l) attenuated neuronal damage (p < 0.01), with evidence of increased cell viability (p < 0.01) and decreased cell morphologic impairment. Furthermore, ALO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 24 publications
(23 reference statements)
2
29
0
Order By: Relevance
“…A 2016 study proposed aloperine and its derivatives as a new class of HIV-1 inhibitors [28] while a more recent study proposed the same as a new class of hepatitis C virus inhibitors [29]. Aloperine exerts a significant antioxidant effect by downregulating the production of ROS and increasing enzymatic activity and total antioxidant capacity in neuronal cells [30]. Another study demonstrated an anti-oxidative stress effect in an Alzheimer's model, where aloperine suppressed ROS and 4-hydroxy-2-nonenal production while increasing mitochondrial membrane potential and adenosine triphosphate production [31].…”
Section: Discussionmentioning
confidence: 99%
“…A 2016 study proposed aloperine and its derivatives as a new class of HIV-1 inhibitors [28] while a more recent study proposed the same as a new class of hepatitis C virus inhibitors [29]. Aloperine exerts a significant antioxidant effect by downregulating the production of ROS and increasing enzymatic activity and total antioxidant capacity in neuronal cells [30]. Another study demonstrated an anti-oxidative stress effect in an Alzheimer's model, where aloperine suppressed ROS and 4-hydroxy-2-nonenal production while increasing mitochondrial membrane potential and adenosine triphosphate production [31].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulated toxic metabolic products could inhibit mitochondrial ATP turnover in neuron cells, leading to “aged” mitochondria with impaired ATP production and increased ROS leakage (Martin et al, 2005). ROS is a well known factor contributing to brain I/R injury (Zeiger et al, 2009; Ma et al, 2015). During I/R, the brain activates its own protection mechanism IPC to remove the ROS generated by I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…The cultures were incubated under the condition of 95% N 2 and 5% CO 2 at 37°C for 2 h as OGD (Ma et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies have shown that the inhibitory effect of apoptosis was related to antiinflammatory and down-regulation of MAPK signaling pathway (Zhao et al, 2017a). Similarly, aloperine (Ma et al, 2015), matrine, and oxymatrine (Zhao et al, 2015a;Zhao et al, 2015b; may have the same protective effect against ischemic neuron apoptosis. As a reversible selective inhibitor of true cholinesterase, huperzine A has been shown to inhibit mitochondrial complexes I-IV, a-ketoglutarate dehydrogenase, and MMP decline after ischemia, which helps to eliminating excessive ROS and Ca 2+ (Zheng et al, 2008).…”
Section: Monomers and Molecular Mechanisms In Regulating Mptp Opennesmentioning
confidence: 97%